Evidence hierarchies relating to hand surgery: current status and improvement. A bibliometric analysis study - Barroso, Thaís Silva; Cavalcante, Marcelo Cortês; Santos, João Baptista Gomes dos; Belloti, João Carlos; Faloppa, Flávio; Moraes, Vinícius Ynoe de (São Paulo Medical Journal, 2017)
BACKGROUND: Hierarchy of evidence is an important measurement for assessing quality of literature. Information regarding quality of evidence within the Brazilian hand surgery setting is sparse, especially regarding whether research has improved in either quality or quantity. This study aimed to identify and classify hand surgery studies published in the two most important Brazilian orthopedics journals based on hierarchy of evidence, with comparisons with previously published data. DESIGN AND SETTING: Bibliometric analysis study performed in a federal university. METHODS: Two independent researchers conducted an electronic database search for hand surgery studies published between 2010 and 2016 in Acta Ortopédica Brasileira and Revista Brasileira de Ortopedia. Eligible studies were subsequently classified according to methodological design, based on the Haynes pyramid model (HP) and the JBJS/AAOS levels of evidence and grades of recommendations (LOR). Qualitative and quantitative data were gathered regarding all studies. Previous data were considered to assess whether the proportion of high-quality studies had improved over time (2000-2009 versus 2010-2016). RESULTS: The final analysis included 123 studies, mostly originating from the southeastern region (78.8%) and private institutions (65%), with self-funding (91.8%). Methodological assessment showed that 15.4% were classified as level I/II using HP and 16.4% using LOR. No significant difference in proportions of high-quality studies was found between the two periods of time assessed (5% versus 12%; P = 0.13). CONCLUSION: Approximately 15% of hand surgery studies published in two major Brazilian journals were likely to be classified as high-quality through two different systems. Moreover, no trend towards quality-of-evidence improvement was found over the last 15 years.